How Firearms May Be Used and what Quantity of Gun Powder May Be Kept, Ordinances of the City of Kenosha, Ordinance no. 8, §1 & §5 (1858). - (:unkn) unknown (General Publisher, 1858)
That no person shall fire or discharge any cannon, rifle, gun, pistol, or fire arms of any description, or fire, explode, or set off any squib, cracker, or other thing containing powder or other combustible or explosive material in any street, alley, or public ground within this city south of a line running through Lemon street from the lake to the west line of the corporation, and east of West Main Street. § 5 No person shall be allowed to keep any gunpowder in any occupied building within the limits of this city without permission of the council;-- and no person shall keep in any such building a greater quantity than ten pounds; which shall be kept in a close tin canister or canisters.
--
Keywords: DISCHARGE